THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND TRANSACTIONAL LEADERSHIP TOWARD EMPLOYEE CREATIVITY ON SMALL-MEDIUM ENTREPRISES IN MANADO - Lintang Winastiani Mangku Dipuro; Joy Elly Tulung; Regina Trifena Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
In developed countries, concern on SMEs is very high. This is due to the fact that SMEs has been considered as the backbone of the economy. However, SMEs are vulnerable to a variety of internal as well as external barriers. As a consequence, governments’ attention to SMEs is mostly in the form of creating conducive environment, entrepreneurship development, access improvement to both domestics and international markets, providing financial facilities, the competitiveness improvement and providing information and supporting network.. The creativity may depend on the employee or situation; an employee may want to be in contact at highest or lowest level although he or she has great potential. The purpose of this study are Transformational Leadership and Transactional Leadership have a simultaneous effect on Employee Creativity at Restaurant-based Small-Medium Entreprises in Manado. The Result shows that the independent variable which are Transformational Leadership and Transactional Leadership simultaneously affect Employee Creativity as the dependent variable.